Magnetization transfer ratio quantifies polyneuropathy in hereditary transthyretin amyloidosis - Hayes, Jennifer; Hegenbart, Ute; Kimmich, Christoph; Hund, Ernst; Purrucker, Jan; Hayes, John M.; Lentz, Stephen I.; Sam, Georges; Jende, Johann; Schönland, Stefan; Bendszus, Martin; Heiland, Sabine; et al. (Annals of Clinical and Translational Neurology, 2020)
Objective To quantify peripheral nerve lesions in symptomatic and asymptomatic hereditary transthyretin amyloidosis with polyneuropathy (ATTRv-PNP) by analyzing the magnetization transfer ratio (MTR) of the sciatic nerve, and to test its potential as a novel biomarker for macromolecular changes. Methods Twenty-five patients with symptomatic ATTRv-PNP, 30 asymptomatic carriers of the mutant transthyretin gene (mutTTR), and 20 age-/sex-matched healthy controls prospectively underwent magnetization transfer contrast imaging at 3 Tesla. Two axial three-dimensional gradient echo sequences with and without an off-resonance saturation rapid frequency pulse were conducted at the right distal thigh. Sciatic nerve regions of interest were manually drawn on 10 consecutive axial slices in the images without off-resonance saturation, and then transferred to the corresponding slices that were generated by the sequence with the off-resonance saturation pulse. Subsequently, the MTR and cross-sectional area (CSA) of the sciatic nerve were evaluated. Detailed neurologic and electrophysiologic examinations were conducted in all ATTRv-PNP patients and mutTTR-carriers. Results Sciatic nerve MTR and CSA reliably differentiated between ATTRv-PNP, mutTTR-carriers, and controls. MTR was lower in ATTRv-PNP (26.4 ± 0.7; P < 0.0001) and in mutTTR-carriers (32.6 ± 0.8; P = 0.0005) versus controls (39.4 ± 2.1), and was also lower in ATTRv-PNP versus mutTTR-carriers (P = 0.0009). MTR correlated negatively with the NIS-LL and positively with CMAPs and SNAPs. CSA was higher in ATTRv-PNP (34.3 ± 1.7 mm3) versus mutTTR-carriers (26.0 ± 1.1 mm3; P = 0.0005) and versus controls (20.4 ± 1.2 mm3; P < 0.0001). CSA was also higher in mutTTR-carriers versus controls. Interpretation MTR is a novel imaging marker that can quantify macromolecular changes in ATTRv-PNP and differentiate between symptomatic ATTRv-PNP and asymptomatic mutTTR-carriers and correlates with electrophysiology.
First published: 25 April 2020
Gesehen am 14.09.2021